Implementation of Bureaucratic Reform at IAIN Palangka Raya - Puspita, Puspita; Ajahari, Ajahari; Wasliman, Iim; Dianawati, Eva (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The implementation of bureaucratic reform in the educational institution system in Indonesia has carried out many substantive transformations in various dimensions. This is because it can be reviewed through the implementation of bureaucratic reforms that focus on services in order to monitor and evaluate performance in the organizational and human resource dimensions. This research is a descriptive qualitative research obtained from interviews. Data collection techniques were carried out by triangulation and data analysis using inductive data reduction, presentation, and verification techniques that emphasized meaning. This study explains that the implementation of bureaucratic reform at IAIN Palangka Raya has gone well in terms of the organizational and human resource dimensions. Although there are several notes such as ease of access to service information at IAIN Palangka Raya which can be improved so that it is right on target. This is expected to generate benefits for the implementation of bureaucratic reform as an effort to develop goal-oriented competencies and skills. In addition, the draft road map on the implementation of policy reforms can be used as a guide and direction for policy or decision makers in implementing bureaucratic reforms.